Memes as Digital Exegesis: Reinterpreting the Prohibition of Muslim Women Traveling Without a Mahram on the Instagram Account @ukhtiakhiantiselfie - Hadhisty Amalia; Ilzam Hubby Dzikrillah Alfani (Noor: Journal of Islamic Studies, 2026)
This article explores how Islamic memes on Instagram serve as digital interpretations of hadith, focusing specifically on the prohibition for Muslim women to travel without a mahram, as presented on the account @ukhtiakhiantiselfie. The study employs Paul Ricoeur’s hermeneutic theoryconsisting of pre-understanding, distanciation, and appropriation to analyze the process of meaning transformation that occurs when hadith is presented visually through social media. Using qualitative content analysis, the research examines how selected memes reflect, reinterpret, or even simplify the original meaning of hadith texts. The findings reveal that meme-based da’wah not only conveys religious messages in a concise and appealing format, but also opens space for new interpretations shaped by the readers’ social context. While some memes tend to reinforce a literal understanding of hadith, others offer implicit room for contextualization. This indicates that meme culture participates in the dynamic construction of religious meaning in the digital era. However, the simplification of sacred texts into visual content poses interpretive challenges, particularly when context and scholarly explanation are omitted. This study concludes that social media can act both as a platform for religious dissemination and as a site of interpretative negotiation between text, media, and audience.